Discovery of a Novel Species of Trichomonasvirus in the Human Parasite Trichomonas vaginalis Using Transcriptome Mining - Manny, Austin; Hetzel, Carrie; Mizani, Arshan; Nibert, Max (Viruses, 2022)
Trichomonas vaginalis is the most common non-viral cause of sexually transmitted infections globally. Infection by this protozoan parasite results in the clinical syndrome trichomoniasis, which manifests as an inflammatory disease with acute and chronic consequences. Half or more isolates of this parasite are themselves infected with one or more dsRNA viruses that can exacerbate the inflammatory syndrome. At least four distinct viruses have been identified in T. vaginalis to date, constituting species Trichomonas vaginalis virus 1 through Trichomonas vaginalis virus 4 in genus Trichomonasvirus. Despite the global prevalence of these viruses, few complete coding sequences have been reported. We conducted viral sequence mining in publicly available transcriptomes across 60 RNA-Seq accessions representing at least 13 distinct T. vaginalis isolates. The results led to sequence assemblies for 27 novel trichomonasvirus strains across all four recognized species. Using a strategy of de novo sequence assembly followed by taxonomic classification, we additionally discovered six strains of a newly identified fifth species, for which we propose the name Trichomonas vaginalis virus 5, also in genus Trichomonasvirus. These additional strains exhibit high sequence identity to each other, but low sequence identity to strains of the other four species. Phylogenetic analyses corroborate the species-level designations. These results substantially increase the number of trichomonasvirus genome sequences and demonstrate the utility of mining publicly available transcriptomes for virus discovery in a critical human pathogen.